Evaluation Of Management Practices Undertaken In Emerging Commercial Fish Farms In Uganda Against Food Safety Control Measures Recommended By International Markets - Bagumire, Ananias; Todd, Ewen C. D.; Nasinyama, George W.; Muyanja, Charles (African Journal of Fisheries Science, 2020)
Selected commercial aquaculture enterprises in Uganda were evaluated for compliance with internationally recommended food safety-related control measures. Food hazard control measures at potential critical control points of: farm siting, farm facilities and premises, and facilities for feed processing and storage, chemical storage, drug storage and waste storage were evaluated. Requirements for traceability, legal and certification, standard sanitation operating procedures and food safety skills for farm workers were the other measures evaluated. On a scale of 0 - 5 where 0 denotes none, 1 very low, 2 low, 3 acceptable, 4 almost total and 5, full compliance, the majority of control points evaluated had average scores below 3, a minimum acceptable level of compliance with international guidelines. Feed processing and storage areas were the most deficient of the potential critical control points. Other significant deficiencies occurred in requirements for traceability of fish and use of on-farm standard sanitation operating procedures. Veterinary drug use, a common problem with aquaculture exports, was not an issue since none of the farms was highly intensive – a practice that would increase the risk of infestation of fish with pathogens and raise the need for use of drugs. The compliance gap requires food safety policy and practice interventions in Uganda and other sub-Saharan countries that plan to export products to highly regulated markets like in the European Union.
Keywords: Uganda, food safety, control measures, aquaculture compliance, sub-Saharan Africa, international market requirements.